THE COMPARATIVE STUDY OF JACK AND THE BEANSTALK AND MOMOTARO: PROPP’S 31 FUNCTIONS ON FOLKTALES - POETRA AJIE BUDIMAN WASKITO (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
THE COMPARATIVE STUDY OF JACK AND THE BEANSTALK AND MOMOTARO: PROPP’S 31 FUNCTIONS ON FOLKTALES Poetra Ajie Language and Literature Department, Faculty of Languages and Arts, Surabaya State University bos.poetra@yahoo.co.id Dr. Ali Mustofa, M.Pd. Language and Literature Department, Faculty of Languages and Arts, Surabaya State University ali_mustofa2012@yahoo.co.id Abstrak Vladimir Propp adalah seorang formalis Rusia yang telah meneliti 100 dongeng Rusia agar bisa menentukan karakter-karakter yang telah menjadi peran utama ditentukan dalam cerita-cerita di setiap dongeng. Dia membagi 31 fungsi dari peran di dalam dongeng-dongeng Rusia yang kemudian disamaratakan dengan cerita rakyat yang lainnya yang berasal dari bagian-bagian yang berbeda di seluruh dunia. Tujuan dari tulisan ini adalah untuk mendiskusikan perbandingan struktur cerita dari dongeng Momotaro dan Jack and the Beanstalk dan membandingkan kesamaan dan perbedaannya. 31 fungsi Propp yang memiliki fungsi sebagai pemandu utnuk peneliti-peneliti cerita rakyat dan kisah-kisah fantasi untuk menelaah structur cerita yang oleh Propp sendiri telah diberi tanda tertentu dan huruf. Setiap cerita memiliki perbedaan struktur, walaupun pada awal cerita memiliki kesamaan. Dalam kisah Jack and the Beanstalk dan Momotaro memiliki kemiripan secara mitologis, yaitu pertempuran manusia melawan raksasa. Banyak cerita rakyat dari berbagai tempat yang berbeda di seluruh dunia yang memiliki kisah kepahlawanan yang menceritakan manusia melawan para raksasayang selalu berakhir dengan kekalahan raksasa. Tapi di setiap cerita memiliki perbedaan, baik dari struktur atau perbedaan latar belakang dan budaya dari pelaku dari setiap cerita, maka dari itu, dalam diskusi kali ini akan di deskripsikan perbedaan secara struktur. Kata kunci: fungsi Propp, struktur naratif, dan cerita rakyat. Abstract Vladimir Propp is a Russian formalist who explored 100 Russian folktales in order to determine the characters who undertook the main roles specified in the fables of the tales. He derived 31 functions of the roles in the Russian tales that were later generalized with other folk tales originating from different parts of the world. The aim of this paper is to study the comparison structure of the story of the Momotaro and Jack and the Beanstalk folktales, and comparing the similarities and differences. Propp’s 31 functions that have the function as a guide for researchers folklore and fantasy stories to analyze the structure of stories by Propp himself has given a sign of the certain symbols and letters. Each story has a different structure, although at the beginning of the story have similarities. In the story of Jack and the Beanstalk and Momotaro has a resemblance in mythological, i.e the battle between human against a giant. Many folk tales from different parts of the world that have the heroic story that tells man against the giants that always ended with the defeat of the giant. But in each story have differences, either structurally or differences in background and culture of the perpetrators of the story of each story, therefore, in this study are described structural differences. Keywords: Propp’s functions, narrative structure, and folktales. INTRODUCTION The tale is a traditional story that grows in society since ancient times, and is derived from the previous generation. events as told in the story is the events that happened in the past. of the classic fairy tale with a verbal folklore genres of story (prose) folk. almost every country has fairytale delivered down from generation to generation. The tales often have elements of the same story from one region to another in a country, even among countries that are located far apart. according to Danandjaja, basically the equation can only be explained by two possibilities, ie: (1) monogenesis, which is followed the discovery of a diffusion process (diffusion) or spread, (2) poligenesis, caused by their own inventions (independent invention) or parallel (parallel invention) of the motives of the same story, in different places as well as the in different times or simultaneously. (Danandjaja, 1986: 56). As oral literature, the majority of folk prose, including fairy tales, do not have standardized rules of storytelling. thus, each speaker can freely provide the title, or any other extras that may be necessary to the story that was brought, so that a similar story could have different names in each region. In many countries in the world that has a fairy - tale patterned almost the same, such as Dutch, German, American, English, Indonesian, and Japanese, some fairy tales from different regions in English turned out to have much in common with fairy tales of Japan (better known as minwa / mukashiBanashi), especially in terms of theme and story line, for example, tales JakaTarub with Hagoromo story, the fable of monkey and the turtle story with saru to kani, Timun mas and sanmai no ofuda and momotaro. In addition to which there are similarities in these stories, there are also differences in the struture of the story who become the hallmark of fairy tales, so it is interesting to study more in narrative structure of Propp’s 31 functions. Although such as a study, in fact, as far as the author to date, there has been little research that conduct narrative structure of these tales, whether contained in western especially in Britain as well as in Japan.In this study, the writer wants to understand about code switching and code mixing and the implicature in Talk show TV program. There are some reasons that make the writer interested to investigate BukanEmpat Mata and HitamPutih program as the subject of the study. METHOD Appropriately, with the purpose of this thesis, revealing the relation between the narrative structures to analyze the stories. The model of this research uses Propp’s 31 functions structure theory that will be analyzed. Meanwhile, the highlight will be focused on the effect of the structure of the folktale, in this case is fairy tales. Thus, the result is found after doing analyzing the narrative structure of Momotaro and Jack and the Beanstalk fairy tales. This thesis uses Propp’s 31 functions theory to analyze the data from the folktales. There are two steps used in this research. The first one is, defining the definition of 31 functions of structure. The second is, relating it in the purpose of doing this research. DATA ANALYSIS AND DISCUSSION This section consists of result and discussion. A literary work can be understood more precise, clear and intact if not put off its intrinsic structure. Based on the conception, then in this description I will first describe the structural analysis of the fairy tale Jack and the Beanstalk and Momotaro. The structural concept which I use as a basic for the text analysis of the two tales is the concept of narrative structure of Vladimir Propp. The following is a narrative theory analysis using the theory of Russian formalist Vladimir Propp. As it has explained in chapter 2 of the 31 functions of narrative structure 100 Russian fairy tales have him thoroughly. As in the following scheme in Momotaro folktales: α Q B C ↑ G H I ↓ initial situation Recognition of the hero The connective incident concent to counteraction Departure Transference to a designatedplace; guidance hero against the villain Victory over the villain Return of the hero Each of symbols and letters are representative of the structure of the story that will be figure out the story line. In every story always begins with the introduction of the characters in the story. In the story of Momotaro, the initial character is introduced grandparents who lived in a village in ancient Japan, then it ended with the victory of Momotaro against the giants that always bother the villagers. In this scheme will be explain the structure of the Jack and the Beanstalk story: α Q β D F B ↑ G O K Pr N W Initial situation Recognition of the hero Absentation The first function of the donor receipt of a magical agent the connective incident departure Transference to a designated place Unrecognized arrival The liquidation of misfortune or lack Pursuit of the hero Solution of a task Wedding The significance of comparing two stories are In the Jack and the beanstalk, the hero was introduced with a young man named Jack. He was a lazy young man who sometimes helps his mother in the field, was initially reserved, likes to eat and brave, symbolized by Q. Momotaro also Jack and the Beanstalk has a different character but, has similar structures of the story, that is initial situation and the recognition of the hero. If in the story of Momotaro directly analyze the connective incident, then it is different with Momotaro connective incident which instantly analyzes. in the story of Momotaro, the connective incident directly because in the structure of the story directly into the beginning of the problems that will face the hero. In the Momotaro story contained the function C that serves as a concent to counteraction which this function describes the role of the hero in eradicating the crime to save someone. In this case were rescued by Momotaro was village and its inhabitants. In the story of Momotaro, no one was donor. In the story of Jack and the Beanstalk, the donor is an old man who met Jack on the way to market. He gave a magical object, a magic bean seeds. Then of the magical object, the departure of Jack climbing the giant tendrils began.While the story of Momotaro there is no magical agent, Momotaro is rely on his own strength. In Transference to a designated place which is symbolized by G, there is little in common, ie the departure of the hero to a place far away from where he lives. In the story of Momotaro, the hero went to his enemies place to cross the valley, across the river, and arrived at the ocean. But it different with Jack and the beanstalk story, In this story, the hero went to his enemy place after receiving a magical object, bean, which later became a huge tendril towering up to the sky and arrived at the giant palace.Same as the previous discussion about the designated place, this time it will discuss about the unrecognized arrival. In the story of Momotaro, no unrecognized function of arrival, he went straight to his enemy and confront them, but it is different in the story of Jack and the Beanstalk. In this story there are initial steps which structured. This is evidenced by the arrival unrcognized which serves to strengthen the functions of the designated place. In the story of Momotaro, the hero against the villain for the sake of the truth. Momotaro fought against the giants because he does not want his village to be bothered by the them. While the story of Jack and the Beanstalk is an irony. Although Jack, indirectly is a hero which defeated the ferocious giant, but the way he did in getting the victory is a criminal way. He did not fight for the truth, but for the sake of fulfilling his greed. At the end of the story Momotaro no marriage after the return of the hero. whereas at the end of the story Jack and the Beanstalk it there. The peak of the conflict in the story Jack and the Beanstalk is a pursuit. Pursuit undertaken by a giant, not found in the story of Momotaro. At first, the story line of Jack and the Beanstalk seem slow, but complete structured. In the story of Momotaro, no chasing each other between the main character with the villain. The Solution of the task in the story of Momotaro is characterized by the destruction of the giants. But I do not regard it as a function of N, but the function of H. Because of the function H is stronger than N in Momotaro, which is the function that describes a direct confrontation with no parts chasing each other in the story. Whereas in Jack and the Beanstalk, the function N is stronger because of Jack's character is not as strong as Momotaro. Jack had to run down the big tendril then arrived in front of his house and then took a big ax and cut the tendril to the ground, and the giant which became his enemy fall and die. CONCLUSION AND SUGGESTION Conclusion After elaborating the structure of the tales of the two, between Momotaro and Jack and the Beanstalk, it can be inferred that the two must have differences, especially if it is looked down on the culture that bases them. Therefore, it should take the formula of the two with regardless the culture. In other word, structure is the basic thing for comparing this, and it finally can be seen at the end of the two that have similarity refers to the structure. The analysis, then see Vladimir Propp’s narrative structure as the razor blade to slice up the pieces of the structure that sharpens to the narrative of the tales. With this tool, the structure at the end can be found and then be analyzed through the characters that establish the narration. Propps, indeed, focuses on the characters as the basic elements who/that moves and triggers every single part of the narrative. In simple word, there is always characters involve in the shifting the plots. It should be understood that it works on prose rather than poetry. Suggestion As an ideology and theory, structuralism Propp's very nice to use, especially for beginners who are just starting to pursue the world of literature who were eager to analyze a story. Propp's 31 functions theory is very good as a basis for understanding the sequence of the story, because basically all literary prose is the same, from the beginning to the end of the story situation. In every story always begins with the initial situation, and Propp mark with the symbol α in which it is easy for the reviewers to understand the story next story sequence that has each symbol which also represents each functions. REFERENCES Bal, Mieke. 1985. Narratology: Introduction to the Theory of Narrative.3rd ed. Trans. Christine van Boheemen. Toronto: University of Toronto Press. Befu, Harumi. 1981. Japan: An Antropological Introduction. Tokyo: Charles E. Tuttle Co. Chan, Tino. 2009. KoleksiLengkapDongengAnakSedunia. Yogyakarta: PustakaWidyatama. Damono, SapardiDjoko. 2005. PeganganPenelitianSastraBandingan. Jakarta: PusatBahasaDepartemenPendidikanNasional. Danandjaja, James. 1997. FolklorJepang :Dilihatdarikacamata Indonesia. Jakarta: PustakaUtamaGrafiti. Dundes, Alan. 1964. The Morphology of North American Indian Folktales.FF Communications. Gakken, 2004.MukashiBanashi.Japan :GakushuKenshuusha. Jabrohim. 1996. PasarDalamPerspektifGreimas.Yogyakarta :PustakaPelajar. Jabrohim. 2003. MetodologiPenelitianSastra.Yogyakarta :HaninditaGrahaWidya. Junji, Kinoshita. 1969. Nihon no Minwa, Mainichi Shinbunsha Encyclopedia Japonica, volume 12, Tokyo :Shogakuken. Matsumura, Akira & Yamaguchi. 1986. KokugoJiten. Tokyo: Akira Bunsha. Matsumura, Akira. Kōzakokugoshi. Tokyo: TaishukaShoten. Propp, Vladimir. 1975. Morphology Of The Folktale. University Of Chicago press. Ratna, NyomanKutha. 2004. Teori, Metode, danTeknikPenelitianSastra. Yogyakarta: PustakaPelajar. Scholes, Robert &Rabkin Eric. 1977. Science fiction: history, science, vision.Oxford University Press. Teeuw, Andries. 1984. Sastradanilmusastra: pengantarteorisastra. Jakarta: Pustaka Jaya. Teeuw, Andries. 1988. Sastradanilmusastra. Jakarta: Pustaka Jaya. http:// Statistics.gov.uk. http://royalsociety.org/ http://www.bbc.co.uk/news/world-europe-18023389. http://www.fordham.edu/halsall/basis/tacitus-germanygord.asp http://www.sste.mmu.ac.uk/ace/ .